Perceived inequality and modes of political participation in South Korea. Issue 3 (8th July 2019) - Lee, Hyun Kyung; Kwon, Hyeok Yong
Abstract : Purpose: The purpose of this paper is to explore whether and how the individual perceptions on income inequality and the inequality of opportunities affect two different modes of political participation, institutional and non-institutional, in South Korea. Design/methodology/approach: The paper analyzes the Korean General Social Survey 2009 and 2014 and estimates logit and OLS models. Findings: The authors find that neither the perceived inequality of income distribution nor the perceived inequality of opportunities affects the likelihood of individuals' vote participation. The authors, however, find that the perceptions of inequality, both in terms of outcomes and opportunities affect citizens' engagement in non-institutional forms of political participation. Originality/value: This study provides a new discussion point about the political consequences of inequality in Korea. This paper distinguishes and analyzes the relative importance of perceived inequality of the outcomes and opportunities in democratic engagements. By considering various types of participation, institutional and non-institutional, this study contributes to deepen our understanding of the factors that drive citizens' democratic political engagements.